The Importance of Diversity and Inclusion in the Humanities Field based on the 1945 Constitution: Celebrating Difference and Promoting Social Justice - Arief Fahmi Lubis (Law Studies and Justice Journal (LAJU), 2024)
The concept of diversity and inclusion in the humanities field has an important role in promoting equality, social justice, and respect for constitutional values. In the Indonesian context, implementing the values ​​of the 1945 constitution is the main focus in developing an inclusive society. This research aims to investigate the influence of diversity and inclusion in the humanities field on the implementation of the values ​​of the 1945 constitution in Indonesia. The research method used is a systematic literature review by collecting articles from reputable international databases such as Scopus and Web of Science. The results of the discussion show that the concepts of diversity and inclusion play a crucial role in creating an inclusive social environment based on constitutional values. The implication of this research is the importance of developing strategies and policies that encourage inclusion and reduce social disparities in Indonesian society.